19.1: Efficiency Enhancement of Indium Phosphide (InP) Based Quantum Dot Light‐Emitting Diodes by Shell Thickness Tuning. Issue 1 (1st July 2013) - Kim, Yohan; Ippen, Christian; Greco, Tonino; Wedel, Armin; Park, Myeongjin; Lee, Changhee; Han, Chul Jong; Kim, Jiwan
Abstract: We investigated the optoelectronic characteristics of QD‐LEDs by tuning ZnS shell thickness of InP/ZnSe/ZnS multishell QDs. Current efficiency of our QD‐LEDs fabricated using thicker ZnS shell of QDs was enhanced up to 4.65 cd/A. It is one of the promising results reported so far for Cd‐free QD‐LEDs.